Application of tactical optimization model and decision-making strategy in football teaching practice - Cheng Wenjie; Fangping Lou; Yuyang Wang (Humanities & Social Sciences Communications)
Abstract The primary objective of this scholarly article is to assess the effectiveness of implementing the tactical optimization model and decision-making strategy in the context of football coaching environments. The study involved the participation of 120 boys from a school in China, enrolled in grades 7–9, and actively engaged in a football program, with an average age of 13.8 years (SD = 1.26). Two subscales from the Tactical-technical and Social Competencies of Football Players Scale (TTSCS) and four subscales from the Melbourne Decision-Making Questionnaire (MDMQ) were employed in the research. The study revealed that the tactical optimization model and decision-making strategy in football empirically substantiated their effectiveness. The intervention group demonstrated improvements in attacking tactical-technical competencies (ATTC) by 10.03 and defensive (DTTC) by 11.35 compared to the control group, where statistically significant changes amounted to only 2.16 in the DTTC subscale. In the decision-making domain within the intervention group, a statistically significant increase in vigilance by 2.92 was noted, while other subscales decreased: hypervigilance by 3.75, transfer of responsibility, and procrastination by 3.45, indicating enhancements.